Investigating cognitive task difficulties and expert skills in e-Learning storyboards using a cognitive task analysis technique - Yusoff, N.M.; Salim, S.S. (2012)
E-learning storyboards have been a useful approach in distance learning development to support interaction between instructional designers and subject-matter experts. Current works show that researchers are focusing on different approaches for use in storyboards, and there is less emphasis on the effect of design and process difficulties faced by instructional designers and subject-matter experts. This study explores problem aspects of the cognitive task and the skills required of subject-matter experts by applying a cognitive task analysis approach from the expert point of view. The result shows that subject-matter experts face difficulties in making decisions on three elements during e-learning course development. The three elements are storyboard templates, prescriptive interactive components, and review process. It is found that the representation skills and decision making of the three elements allows subject-matter experts to decide on alternatives of the task process. The result also indicates that it is important to leverage the design and process skills of subject-matter experts as it affects their interaction with instructional designers. Three recommendations are made: training development, prescriptive interactive components development, and interaction design document development. A new framework can be recommended to train subject-matter experts as e-learning storyboard users, and in turn provide for effective interaction between them and instructional designers. (C) 2011 Elsevier Ltd. All rights reserved.